Pengembangan E-Modul Berbasis Flipbook Maker pada Kursus Perawatan Tangan, Kaki dan Kuku - Anisa Taqwina; Rahmiati; Linda Rosalina; Refdinal (Universitas Pendidikan Ganesha, 2022)
The learning objectives of hand, foot and nail care for students of makeup and beauty education is not sufficient and not optimal. Therefore, there is a need for innovation in learning, especially hand care and foot care learning materials. ICT-based modul is solution to overcome this problem. This study aims to develop e-module learning media based on flipbook maker in the department of cosmetology and beauty. The methodology used is Research and Development (R&D) with the Four D procedure through the stages of define, design, develop and disseminate. The research subjects were 3 media experts and 3 material experts. While the research subjects in the practical test were 2 lecturers and 20 students of the department of cosmetology and beauty. Data were obtained by using test instruments to test the effectiveness and non-test instruments to test the validity and practicality of the research process. Data analysis uses V Aiken calculations for product validation, percentage formulas for practicality and effectiveness. The results of this research show there is a significant comparison of students' understanding of hand, foot and nail care using flipbook maker-based e-module learning media. Based on all these analyzes it was concluded that the e-module based on flipbook maker was stated to be valid, practical and effective as one of the learning media for the hand, foot and nail care course.